The Perceptions and Tendencies of Judges Religious Court In Using the Kitab Kuning (Books of Fiqh) in Indonesia - Irawan, Aris; Fitri Wahyuni; Reza Hanifa; Asneliwarni; Suryani, Rias Wita (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2022)
This research investigates the judges’ perception and tendency to refer to the Books of Fiqh (Kitab Kuning). This research focuses on sharia economic dispute settlement in Indonesian religious courts. The research method used combines normative legal and empirical socio-legal research. The results found that the perception and tendency of judges towards several sources of legal rules in assessing, weighing, and deciding a sharia economic case in the Indonesian Religious Courts, did not always rely on one KHES as a material source. In Indonesian law, judges cannot use only one source in resolving sharia economic disputes, such as the Book of Fiqh (Kitab Kuning) only. However, it is an equally important combination, and it can be seen from several decisions of the Religious Courts in Indonesia.